Alternative salt bridge formation in Aβ—a hallmark of early-onset Alzheimer's disease? - Schledorn, Maarten; Meier, Beat H.; Böckmann, Anja (Frontiers in Molecular Biosciences, 2015)
Recently the 3D structure of the Osaka mutant form (E22Δ) of Amyloid-β1-40 has been determined. We here compare the NMR chemical-shift with the published shifts of a brain-seeded form of wild-type Aβ and suggest that the determined mutant fold is accessible to the wild-type protein as well, with small conformational adaptations which accommodate the E22 residue missing in the Osaka mutant. In addition, we illustrate how other mutants could also conform to this model. The stabilization of the N-terminal part of the protein via an intermolecular salt bridge to Lys28 may represent a common structural motif for the mutants which are related to early-onset Alzheimer disease. This feature might connect to the observed increased toxicity of the mutant forms compared to wild-type Aβ1-40, where the salt bridge involving Lys28 is intramolecular.